Efeito dos parâmetros de eletrodeposição na resistência à corrosão de revestimentos de Zn-Sn e Zn-Sn-In - Pereira, Juliermes Carvalho (2021)
The influence of the electrodeposition operational parameters on the morphology, chemical composition of the layer, on the efficiency of the electrodeposition process and on the corrosion, resistance was investigated for the Zn-Sn and Zn-Sn-In coatings. These coatings were obtained on 1020 carbon steel in a eutectic solvent medium based on choline chloride and ethylene glycol in a molar ratio of 1:2. For comparison purposes, Zn coatings were obtained under the same conditions. For these coatings, the Zn content increased with the concentration of Zn2+ species in the bath, with the electrodeposition temperature and with the displacement of the electrodeposition potential to more negative values. The addition of In to the Zn-Sn layers promoted greater grain size refinement and an increase in corrosion resistance in 3.5% NaCl compared to Zn and Zn-Sn coatings. All coatings obtained at potential more negative than –1.3 V were porous and poorly adherent to the substrate. The X-ray diffractograms showed that there was no formation of intermetallic phases in the Zn-Sn coatings, while in the ternary electrodeposit the In-Sn4 phase was detected, which was also confirmed by the galvanostatic electrodissolution tests. Finally, the Zn64Sn23In13 layer showed the highest corrosion resistance.